Hurrah, I.A. & Wagh, V.V. (2021) Revisiting the taxonomy of Geranium kishtvariense (Geraniaceae) & notes on neotypification. Phytotaxa 516 (2): 169–177. - Hurrah, Imtiyaz Ahmad; Wagh, Vijay Vishnu (Phytotaxa, 2021)
N/A